2011
DOI: 10.1103/physrevb.84.245310
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular magnetic anisotropy and high spin-polarization ratio in epitaxial Fe-N thin films

Abstract: We have demonstrated a general framework for realizing and modulating perpendicular magnetic anisotropy in a rare-earth-element and heavy-metal -free material system. Using GaAs(001)/Fe(001) template, we have developed a synthesis scheme to produce epitaxial body center tetragonal Fe-N with (001) texture. By varying the N doping concentration, the crystal tetragonality (c/a) can be tuned in a relatively wide range. It is found that the Fe-N layer developed a strong perpendicular magnetic crystalline anisotropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 26 publications
10
63
0
1
Order By: Relevance
“…Experimentally, the large tetragonality can be obtained in films, where it can be tuned by the nitrogen concentration. 37 However, according to our results above, doping bulk Fe 16 N 2 in a way that increases c/a may lead to MAE increase. The MAE and AMAE are well correlated as shown in Fig.…”
Section: Magnetic Anisotropymentioning
confidence: 50%
“…Experimentally, the large tetragonality can be obtained in films, where it can be tuned by the nitrogen concentration. 37 However, according to our results above, doping bulk Fe 16 N 2 in a way that increases c/a may lead to MAE increase. The MAE and AMAE are well correlated as shown in Fig.…”
Section: Magnetic Anisotropymentioning
confidence: 50%
“…X-ray diffraction (XRD) revealed that the films grow epitaxially with the c-axis oriented perpendicular to the film surface, and with the epitaxial relation α in reasonable agreement with previous results. 6,7 Magnetic force microscopy (MFM) measurements in demagnetized state and zero field at room temperature confirm this physical picture. A sample with small c/a value (c/a = 1.01) and low K u showed almost no magnetic signal (see Fig.…”
Section: -13mentioning
confidence: 79%
“…But more than that for α ′ -Fe 8 N x thin films experimentally also a switching of the magnetization from in-plane direction to out-of-plane (perpendicular) direction along the crystallographic c-axis has been observed, 7,8 but remained elusive to theoretical understanding. Tetragonal distortions alone are not enough to induce PMA in α-Fe.…”
Section: -13mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to dominant Fe-Fe interactions, N atoms are weakly bonded to Fe atoms and preserve the structure and the magnetic properties of Fe [11]. Magnetic properties of interstitial Fe-N supersedes pure Fe, giving rise to interesting effects such as giant magnetic moment [12][13][14], soft magnetic properties [15,16], perpendicular magnetic anisotropy [14,17,18], etc. However, interstitial Fe-N with such a large amount of N are thermodynamically unfavorable [11], and unlike iron oxides, their enthalpy of formation ( H • f ) is at least an order of magnitude more, and even positive as in the case of α -Fe 16 N 2 ( H • f = 85 ± 47) [11].…”
Section: Introductionmentioning
confidence: 99%